Differential impact of TGFβ/SMAD signaling activity elicited by Activin A and Nodal on endoderm differentiation of epiblast stem cells. Issue 1 (1st February 2022) - Knowles, Hilary; Santucci, Nicole; Studdert, Joshua; Goh, Hwee Ngee; Kaufman‐Francis, Keren; Salehin, Nazmus; Tam, Patrick P. L.; Osteil, Pierre
Summary: Allocation of cells to an endodermal fate in the gastrulating embryo is driven by Nodal signaling and consequent activation of TGFβ pathway. In vitro methodologies striving to recapitulate the process of endoderm differentiation, however, use TGFβ family member Activin in place of Nodal. This is despite Activin not known to have an in vivo role in endoderm differentiation. In this study, five epiblast stem cell lines were subjected to directed differentiation using both Activin A and Nodal to induce endodermal fate. A reporter line harboring endoderm markers FoxA2 and Sox17 was further analyzed for TGFβ pathway activation and WNT response. We demonstrated that Activin A‐treated cells remain more primitive streak‐like when compared to Nodal‐treated cells that have a molecular profile suggestive of more advanced differentiation. Activin A elicited a robust TGFβ/SMAD activity, enhanced WNT signaling activity and promoted the generation of DE precursors. Nodal treatment resulted in lower TGFβ/SMAD activity, and a weaker, sustained WNT response, and ultimately failed to upregulate endoderm markers. This is despite signaling response resembling more closely the activity seen in vivo . These findings emphasize the importance of understanding the downstream activities of Activin A and Nodal signaling in directing in vitro endoderm differentiation of primed‐state epiblast stem cells.